The Challenge of Reducing Non-Revenue Water in Developing Countries--How the Private Sector Can Help : A Look at Performance-Based Service Contracting - Kingdom, Bill; Liemberger, Roland; Marin, Philippe (World Bank, Washington, DC, 2014)
This study explains that one of the major issues affecting water utilities in the developing world is the considerable difference between the amount of water put into the distribution system and the amount of water billed to consumers (also called "non-revenue water" [NRW]). High levels of NRW reflect huge volumes of water being lost through leaks, not being invoiced to customers, or both. It seriously affects the financial viability of water utilities through lost revenues and increased operational costs. In this report, a number of case studies, taken from some of the largest and most recent performance-based NRW contracts, are studied and discussed in terms of their technical and financial performance. Lessons learned from the case studies are analyzed, showing the potential benefits of NRW performance-based service contracting with the private sector. This paper was prepared as part of a Public-Private Infrastructure Advisory Facility (PPIAF)-financed study to investigate opportunities for the use of the private sector to assist water utilities in developing countries in reducing non-revenue water. This study indicates that the private sector help ailing public sector utilities in developing countries reduce NRW even though the performance- based service contracting approach described should not be seen as a substitute for overall sector reform. The case studies, while limited in number, provide examples of both good ideas and those to be avoided-but hopefully enough to help a utility and its consultants devise better cost-effective contractual arrangements suited to their conditions.